Surgical treatment of locally advanced papillary thyroid carcinoma after response to lenvatinib: A case report. (2017) - Tsuboi, Mitsuhiro; Takizawa, Hiromitsu; Aoyama, Mariko; Tangoku, Akira
Highlights: There is no established neoadjuvant therapy for advanced DTC. We report the case of a locally advanced DTC that was invaded the trachea, the muscular layer of the esophagus, and the right internal jugular vein. After response to lenvatinib, the tumor was resected. Abstract: Introduction: Differentiated thyroid carcinomas (DTC) have good prognoses after complete resection. Nevertheless, when DTC is associated with an aerodigestive invasion, curative surgery is difficult to perform. However, there is no established neoadjuvant therapy for advanced DTC. Presentation of case: A 73-year-old man with thyroid papillary carcinoma was referred to our hospital. A computed tomography examination revealed a tumor in the upper right lobe of the thyroid, and multiple bilateral enlarged lymph nodes in the neck, involving the surrounding structures. The enlarged lymph node at the right upper neck was suspected to have invaded the right internal jugular vein, and the left paratracheal lymph node was suspected to have invaded the cervical esophagus and trachea. The tumor was considered resectable; however, surgery would have been highly invasive. Therefore, we initiated neoadjuvant therapy with lenvatinib. After administration of lenvatinib, the tumor decreased in size by 84.3% and the cervical lymph nodes by 56.0%. The patient underwent a total thyroidectomy, modified neck dissection, a resection of the muscular layer of the esophagus, and a tracheal sleeve resection and reconstruction. Discussion: The SELECT trial demonstrated that lenvatinib had high response rate with short response time, in patients with radioiodine-refractory DTC. The results suggested that lenvatinib could be effective as neoadjuvant therapy. Conclusion: For an advanced DTC that requires removal through invasive surgery, preoperative lenvatinib treatment might be one of the options for a less invasive surgery.